Consumer Confusion in the UK Skin Care Market - Ng, Man Wai (2007)
Consumer confusion exists in many consumer markets and this study examines the UK skin market in particular. By reviewing the skin care market in UK, it is found that the consumer may be confused about who makes the products and mistaken attribute their dissatisfaction with the wrong products to the manufacturer of the original one. Most customers reply on the trademark as the indicators of COOP. Thus, it is necessary to investigate the literature on trademark, trademark infringement and passing off which relate to the consumer confusion about the COOP and the potential sources of such confusion. The objectives of this study aim to investigate the magnitude of the magnitude of purchaser confusion and identify its sources as well as to estimate the extent of normal confusion regarding the UK skin care market.